Philippine Museum of the Earth Sciences - Encarnacion, Isabel Paula U.
Despite being at the hotspot of experiencing various natural phenomena and of having a remarkable geologic history; the Philippines lags behind its neighboring countries in terms of research on the knowledge and information that is concerned with the earth sciences. Though there exists a competent and adept academic community dedicated in these fields in the country, the most lay-people have yet to develop a consciousness in terms of realizing the significance of these areas of study in our daily lives. It is therefore determined that a facility is needed to help the scientific community reach out to the public in a way that helps both parties in terms of developing the body of knowledge in the country. The Philippine Museum of the Earth Sciences was therefore designed as an outlet in which the experts can communicate to the lay-people of their knowledge through different stimuli. Located within and near government science institutions in Quezon City, this museum will serve as country's main and largest repository of Philippine geological, paleontological, and mineralogical samples in which the visitors will get to see and experience beyond the limits of a classroom or a textbook.